2002
DOI: 10.1519/1533-4287(2002)016<0271:flofrb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Levels of Firefighter Recruits Before and After a Supervised Exercise Training Program

Abstract: Federal law prohibits pre-employment physical examination of firefighter recruits, but these workers must perform intense exercise in arduous environments. Components of physical fitness of rookie firefighters (n = 115; 104 men, mean +/- SD: age = 28.3 +/- 4.3 years; height = 1.76 +/- 0.07 m; weight = 83.2 +/- 13.9 kg; percent body fat = 17 +/- 8%) were measured upon being hired and following a 16-week exercise training program (1 h.d(-1), 3 d.wk(-1)) designed to improve physical fitness. Maximum aerobic capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 0 publications
3
47
0
1
Order By: Relevance
“…Within the past few decades, there has been growing interest in promoting physical fitness for firefighters (Garver et al, 2005). General health promotion (Barnard and Anthony, 1980) and exercise programs (Adams et al, 1986;Barnard and Anthony, 1980;Roberts et al, 2002) have noted improvements in physical fitness. Research has also found correlations between overall physical fitness and performance of job-related (functional) tests (Punakallio et al, 2004;Rhea et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Within the past few decades, there has been growing interest in promoting physical fitness for firefighters (Garver et al, 2005). General health promotion (Barnard and Anthony, 1980) and exercise programs (Adams et al, 1986;Barnard and Anthony, 1980;Roberts et al, 2002) have noted improvements in physical fitness. Research has also found correlations between overall physical fitness and performance of job-related (functional) tests (Punakallio et al, 2004;Rhea et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…While in 1975 a VO 2max >33 ml/kg/min was recommended for fire fighters [1], more recent research [4,19,20] suggested higher values of aerobic power (VO 2max >45 ml/kg/min) to successfully complete firefighting interventions [21]. On the other hand, few indications are available regarding the standards needed for strength to safely meet the demand of the most strenuous fire-fighting tasks such as a lifting, pulling, working and carrying objects [4,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Participants will continue to be followed at 6-month intervals for an additional 18 months to determine how fitness and injury outcomes are affected long term. This is a strong benefit of the study design, as long-term effectiveness of many fire service fitness and injury interventions are often unknown (Cady et al, 1985;Conrad et al, 2005;Roberts et al, 2002).…”
Section: Monitoring and Evaluationmentioning
confidence: 99%
“…And although firefighter physical fitness levels are comparable to those of the general population, both current firefighters and new recruits often do not possess the level necessary for the rigors of the occupation (Guidotti, 1992;Roberts, O'Dea, Boyce, & Mannix, 2002;Swank, Adams, Barnard, Berning, & Stamford, 2001). Firefighters as an occupational group also have a high prevalence of sedentary lifestyle, obesity, hypertension, and high total cholesterol (Byczek, Walton, Conrad, Reichelt, & Samo, 2004;Guidotti, 1992Guidotti, , 1995, and there is consistent evidence that inadequate physical fitness places firefighters at direct risk for a cardiac event, and indirectly through elevated body mass index (BMI), triglyceride levels, and blood pressure (Byczek et al, 2004;Kales et al, 1998Kales et al, , 1999.…”
mentioning
confidence: 99%
See 1 more Smart Citation